Chapter Gli archivi dei movimenti e di altri soggetti sociali: alcuni esempi in Toscana - Del Vivo, Caterina (Strumenti per la didattica e la ricerca, 2021)
The contribution offers an overview of the archives of the movements preserved in Tuscany and of the critical issues of their conservation and enhancement.